A Suppressor Mutation Partially Reverts the xantha Trait via Lowered Methylation in the Promoter of Genomes Uncoupled 4 in Rice - Jiang, Meng; Liu, Yanhua; Li, Ruiqing; Zheng, Yunchao; Fu, Haowei; Tan, Yuanyuan; Møller, Ian Max; Fan, Longjiang; Shu, Qingyao; Huang, Jianzhong (Frontiers in Plant Science, 2019)
The xantha trait of a yellow leaf rice mutant (HYB), controlled epigenetically by elevated CHG methylation of the genomes uncoupled 4 (OsGUN4) promoter, has reduced chlorophyll content, altered tetrapyrrole biosynthesis and deregulated transcription of photosynthesis-associated nuclear genes (PhANGs) compared to its wild-type progenitor LTB. In the present study, we identified a suppressor mutant (CYB) of HYB and characterized its genetic, molecular and physiological basis of the mutant phenotype. We found that the light green phenotype of CYB was caused by a suppressor mutation in an unknown gene other than OsGUN4. Compared to HYB, the CHG methylation in the OsGUN4 promoter was reduced, while OsGUN4 transcript and protein abundance levels were increased in CYB. The contents of total chlorophyll and its intermediate metabolites (except protoporphyrin IX) in CYB plants were intermediate between HYB and LTB. The expression levels of 30 genes involved in tetrapyrrole biosynthesis in CYB were all partially reverted to those of LTB, so were the PhANGs. In summary, a suppressor mutation caused the reversion of the xantha trait via reducing CHG methylation in OsGUN4 promoter.